Individuals' Awareness of and Willingness to Accept Hospital-at-Home Services and Related Factors: A Cross-Sectional Study - Xu, Siyu; Wang, Jingjun; Wang, Ya; Wang, Mengmeng; Huang, Xia; Huang, Hao (Frontiers in Public Health, 2022)
Introduction Hospital-at-home (HaH) services have become increasingly popular. However, the experience of HaH implementation in Asia is inadequate. Therefore, the purpose of this study was to investigate individuals' willingness to accept HaH services and the potential related factors. Methods The researchers visited households to select appropriate participants. An online questionnaire survey was conducted among the inhabitants of selected communities. An individual's awareness, willingness to accept HaH services, and demands such as ideal service providers and more detailed information to accept HaH care were investigated. The outcome measure was the willingness to accept HaH services. Chi-square tests and logistic regression models were used to analyze the factors. Results A total of 622 subjects participated in this study. The findings indicate that 55.9% of the participants were not aware of HaH services, while most of the subjects (88.4%) were willing to accept them. Regression models indicated that having health insurance (OR = 2.170, 95% CI: 1.003–4.697), an awareness of the necessity of HaH services (OR = 4.721, 95% CI: 2.471–9.019), very much hoping staff from central hospitals would be service providers (OR = 20.299, 95% CI: 5.718–72.068), and somewhat hoping that staff from central hospitals would be service providers (OR = 9.139, 95% CI: 2.714–30.775) were the factors associated with a greater willingness to accept HaH services. Conclusion The study indicates that compared to the awareness of HaH care, residents had a greater willingness to accept such care. The willingness to utilize HaH services among individuals was associated with enabling factors, predisposing factors, and HaH-related demand factors.